Mera : tidebreaker - Paige, Danielle (Novelist); Byrne, Stephen (Comic book artist); Calderon, David; Reed, Joshua (2019)
"Princess Mera is teenage royalty and heir to the throne of Xebel, a penal colony ruled by the other not-so-lost land under the sea, Atlantis. Her father, his court and the entire kingdom are expecting her to marry and introduce a new king, but Mera is destined to wear a different crown. When the Xebellian military plots to overthrow Atlantis and break free of its oppressive regime, Mera seizes the opportunity to take control over her own destiny by assassinating Arthur Curry--the long-lost prince and heir to the kingdom of Atlantis. But her mission gets sidetracked when Mera and Arthur unexpectedly fall in love. Will Arthur Curry be the king at Mera's side, or will he die under her blade as she attempts to free her people from persecution?"--
Includes an excerpt from Under the moon : a Catwoman tale
Keywords: Atlantis (Legendary place) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Princesses -- Comic books, strips, etc; Princes -- Comic books, strips, etc; Graphic novels; Young adult fiction